Tax Avoidance in Indonesian Infrastructure Companies: Roles of CEO Narcissism, Related Party Transactions, and Audit Quality - Oon Sarwono; Fadjarenie, Agustin (LifeSciFi, 2025)
Taxation serves as one of the most crucial sources of state revenue for financing various development programs and public services This study examines the effect of CEO narcissism, related party transactions, and audit quality on tax avoidance. The sample consists of 34 infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. The analysis uses panel data regression with a Fixed Effect model, selected based on Hausman and Chow test results. Findings show that CEO narcissism and related party transactions have a significant positive effect on tax avoidance, while audit quality has a significant negative effect. This study expands existing literature by integrating behavioral, transactional, and governance dimensions into a unified framework for analyzing tax avoidance. It is among the few studies applying a visual-based proxy CEO photo prominence to measure narcissism in the Indonesian context. A noteworthy context of this study is the regulatory exemption from the 4:1 debt-to-equity ratio limit granted to infrastructure firms in Indonesia, allowing them greater flexibility in financing through related party loans. While supporting development goals, this exemption also raises the risk of tax avoidance. By highlighting how personality traits, intra-group financing, and auditor oversight interact, this study offers insights for improving corporate governance and tax policy, particularly in strategic sectors like infrastructure.